Interface Based on Electrooculography for Velocity Control of a Robot Arm - Eduardo Iáñez; José M. Azorín; Eduardo Fernández; Andrés Úbeda (Applied Bionics and Biomechanics)
This paper describes a technique based on electrooculography to control a robot arm. This technique detects the movement of the eyes, measuring the difference of potential between the cornea and the retina by placing electrodes around the ocular area. The processing algorithm developed to obtain the position of the eye at the blink of the user is explained. The output of the processing algorithm offers, apart from the direction, four different values (zero to three) to control the velocity of the robot arm according to how much the user is looking in one direction. This allows controlling two degrees of freedom of a robot arm with the eyes movement. The blink has been used to mark some targets in tests. In this paper, the experimental results obtained with a real robot arm are shown.